Carleman estimates, observability inequalities, and null controllability for interior degenerate nonsmooth parabolic equations - Fragnelli, Genni, 1975-; Mugnai, Dimitri, 1972- (Memoirs of the American Mathematical Society ;, 2016)
We consider a parabolic problem with degeneracy in the interior of the spatial domain, and we focus on observability results through Carleman estimates for the associated adjoint problem. The novelties of the present paper are two. First, the coefficient of the leading operator only belongs to a Sobolev space. Second, the degeneracy point is allowed to lie even in the interior of the control region, so that no previous result can be adapted to this situation; however, different cases can be handled, and new controllability results are established as a consequence.